VISUALISASI R DALAM PEMBELAJARAN DISTRIBUSI NORMAL - Joko Sungkono; Andhika Ayu Wulandari; M. Wahid Syaifuddin (LPPM Universitas Widya Dharma, 2023)
Learning about the normal distribution is closely related to function formulas and theories dealing with mathematical symbols. This understanding of mathematical normal distribution theories often creates its own obstacles for students. To provide an easier understanding, a visualization is needed in learning, so that students have a clearer picture of the normal distribution. Through the simulation method visualization of the normal distribution theories is carried out. The simulation was carried out using the help of software R. Through the simulation, students can find out the curve of the normal distribution density function and can modify the desired parameters. This can clarify some of the properties of the normal distribution density function. Simulations were also carried out on the cumulative distribution function to provide a clearer picture of the nature of the cumulative distribution function. The transformation of a normally distributed random variable with parameter µ and variance σ2 into a standard normally distributed random variable can also be explained visually. Through this visualization, students have a clearer picture to support theoretical learning mathematically. Furthermore, students have a better understanding in learning material about the normal distribution